2015
DOI: 10.9734/indj/2015/17789
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Difficulties in Adolescence: Psychopathology and Family Interactions

Abstract: Introduction: Several studies on developmental age have investigated aspects relating to emotional competence, and alexithymia in particular, showing that it is associated with behavioral problems in childhood and adolescence. Some such research has focused on the relationship between emotional difficulties and family interactions assuming a link between the quality of family relationships and a child's emotional competence. Subjects and Methods:The aims of the present study were: 1) to compare a group of psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
(15 reference statements)
4
5
0
1
Order By: Relevance
“…Although preliminary, these results seem to be in line with literature evidences (Palmer et al, 2013;Gatta et al, 2015a) which show that patients with internalizing disorders seem to respond quicker and better to psychotherapeutic treatment than those with externalizing problems. Indeed, patients with externalizing problems seem more difficult to treat and to involve in research studies and, furthermore, it appears more difficult to build a working alliance with them (Midgley & Kennedy, 2011).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Although preliminary, these results seem to be in line with literature evidences (Palmer et al, 2013;Gatta et al, 2015a) which show that patients with internalizing disorders seem to respond quicker and better to psychotherapeutic treatment than those with externalizing problems. Indeed, patients with externalizing problems seem more difficult to treat and to involve in research studies and, furthermore, it appears more difficult to build a working alliance with them (Midgley & Kennedy, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…However, what seems to be confirmed from our data is that adolescents with internalizing problems, somatic complaints and attention difficulties belong to families with high levels of conflict between parents (Gatta et al, 2015a). In addition, in a case control study run in 2015 on the transmission of the parent-adoThe Lausanne Trilogue Play within the outcome evaluation in infant mental health: a preliminary report N o n -c o m m e r c i a l u s e o n l y lescent attachment bond (Gatta et al, 2015b) results confirmed the prevalence of dysfunctional parental attachment bonds in adolescents with psychopathological issues, stressing the important role of interactive family patterns as risk or protective factors for the onset of psychiatric disorders.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…More specifically, as far as it concerns the application of the LTP to the feeding situation, the presence of such good indexes of internal consistency in all the variables considered appears to support the suitability of the application of the procedure to contexts which are different from the original one represented by the play situation. This result appears in line with previous studies that adapted the LTP procedure according to family culture, children’s age, peculiarities in development, and which did not result to compromise the internal consistency and the reliability of the coding system (Hedenbro et al, 2006; Miscioscia et al, 2013; Gatta et al, 2014, 2015). …”
Section: Methodssupporting
confidence: 91%